Multifunctional optical devices based on 5x5 multimode interference on an SOI platform for all-optical computing applications - - Thanh Le, Trung (Vietnam Journal of Science and Technology, 2017)
The design of multifunctional devices based on Multimode  Interference  (MMI) structures for all-optical computing applications is presented in this paper. Based on the self-imaging effect in a multimode silicon planar waveguide, a variety of all-optical devices such as all-optical beam splitters, combiners, optical XOR and OR logic gates can be realized. The analytical expression describing  the  characteristics  of  the  proposed  devices  is  analysed  and derived. Designs  of  the proposed devices on a silicon on insulator (SOI) platform are then verified and optimised using numerical simulation methods